MEASURING OF AIRWAYS RESISTANCE BASED ON INTERRUPTER TECHNIQUE IN PRE-SCHOOLCHILDREN - N.V. Malyuzhinskaya; M.V. Garina; A.V. Shatalin; N.A. Smirnov; V.A. Gorbunova; A.V. Razvalyayeva (Вопросы современной педиатрии, 2010)
Authors give information on limits of population norm for expiratory and inspiratory resistance by the interrupter technique indices (RINTexp and RINTinsp accordingly) in 214 healthy children 3–6 years old. Estimation of RINT was performed with spirograph Super Spiro with MicroRint module. Parameters of RINTexp and RINTinsp are similar in boys and girls. RINTexp depends on height of a child. Information on limits of normal rates is presented in this article, and this data can be used in diagnostics of respiratory pathology. Key words: children, age, resistance of airways, RINT, norm.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(5):30-34)